2011
DOI: 10.3844/ajabssp.2011.114.121
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Variability and Races of <i>Fusarium oxysporum</i> f.sp. ciceris Associated with Chickpea (<i>Cicer arietinum</i>) Crops

Abstract: Problem statement:Mexico is the third largest producer and exporter of chickpea (Cicer arietinum), with the states of Sinaloa and Sonora accounting for 70 and 20% of Mexico's production, respectively. The most damaging disease affecting this species is caused by Fusarium oxysporum f.sp. Ciceris (FOC), which causes losses of up to 60% in Sonora. The objective of this study was to isolate and characterize the phenotype and genetics of FOC collected from affected chickpea plants in northwestern Mexico and to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
2
10
0
2
Order By: Relevance
“…Races 0, 1A, 1B/C, 5 and 6 have been reported in the Mediterranean region and in California (Halila and Strange, 1996;Jim enez-Díaz et al, 1993a;Jim enez-Gasco and Jim enezDíaz, 2003;Jim enez-Gasco et al, 2001), while races 1A, 2, 3, and 4 have been reported in India (Haware and Nene, 1982b). Recently, races 2 and 3 were reported in Turkey (Bayraktar and Dolar, 2012;Dolar, 1997), races 2, 3, and 4 in Ethiopia (Shehabu et al, 2008), races 0, 1B/C, 5 and 6 in northwestern Mexico (Arvayo-Ortiz et al, 2011), and races 0, 1B/C, 4 and 5 in Iraq (Al-Taae et al, 2013).…”
Section: Differential Chickpea Linementioning
confidence: 94%
See 1 more Smart Citation
“…Races 0, 1A, 1B/C, 5 and 6 have been reported in the Mediterranean region and in California (Halila and Strange, 1996;Jim enez-Díaz et al, 1993a;Jim enez-Gasco and Jim enezDíaz, 2003;Jim enez-Gasco et al, 2001), while races 1A, 2, 3, and 4 have been reported in India (Haware and Nene, 1982b). Recently, races 2 and 3 were reported in Turkey (Bayraktar and Dolar, 2012;Dolar, 1997), races 2, 3, and 4 in Ethiopia (Shehabu et al, 2008), races 0, 1B/C, 5 and 6 in northwestern Mexico (Arvayo-Ortiz et al, 2011), and races 0, 1B/C, 4 and 5 in Iraq (Al-Taae et al, 2013).…”
Section: Differential Chickpea Linementioning
confidence: 94%
“…F. oxysporum f. sp. ciceris is one of the few formae speciales of monophyletic origin in the F. oxysporum complex of the Gibberella clade, most of which are polyphyletic (Baayen et al, 2000;Demers et al, 2014;Kistler, 2001;Jim enez-Gasco et al, 2002;O'Donnell et al, 1998). This fungus is pathogenic only on Cicer spp.…”
mentioning
confidence: 95%
“…The genetic variability of the strains was not correlated with sampling site. Similarly, Arvayo-Ortiz et al (2011) observed that morphological variability in Fusarium oxysporum f.sp. ciceris was high in the main chickpea producing regions of northwestern Mexico and was not a function of the physical or chemical properties of the soil; nor it was related to the geographic location of the cropfields.…”
Section: Discussionmentioning
confidence: 77%
“…For Mexico: Sinaloa and Sonora, the authors of this study determined 4 strains, being pathotypes of yellowing (R0, R1B/C) and wilting (R5, R6). FOC morphological variability was high and is not determined by the geographic region of crop fields or the physical and chemical properties of soil (Arvayo-Ortiz et al, 2011). This study was the first record of strains of FOC by specific PCR for Mexico.…”
Section: Introductionmentioning
confidence: 80%
“…The inoculums was prepared from six strains (S1-S6) obtained previously by the authors (Arvayo-Ortiz et al, 2011), from the most important chickpea regions of Sonora: La Costa de Hermosillo and Valle del Yaqui (Table 1). Three strains belonged to race 0 (yellowing path type) and three to race 5 (wilting path type) of Fusarium oxysporum f. sp.…”
Section: Preparation Of Inoculamentioning
confidence: 99%